How can we keep our patients safe? Managing cyber-threats post-pandemic - Neumeier, Melanie (My University, 2023)
The COVID-19 pandemic has created unprecedented challenges for the healthcare industry worldwide, including an increase in cyberattacks. Canadian hospitals have been particularly hard hit by ransomware attacks, which have surged during the pandemic. Ransomware attacks can have serious consequences, including the disruption of patient care and compromise of sensitive patient data. There have been several recent ransomware attacks on Canadian hospitals that highlight the seriousness of this threat. Attacks on the University of Ottawa Heart Institute and the Newfoundland and Labrador health system in 2021,Toronto Sick Kids Hospital in December 2022, and Ross Memorial Hospital in February 2023are just some examples of recent cyberattacks on healthcare targets (CBC News, 2021; Mosleh, 2023; Solomon, 2022). And while LockBit apologized for the attack on Toronto SickKids Hospital in December (Mosleh, 2023), the increase in frequency and scope of ransomware attacks on our healthcare system is a national concern. The Communications Security Establishment, the federal government’s IT security agency, has noted that ransomware and other malware attacks are not only becoming more frequent, but are also becoming more sophisticated, and hospitals have some unique factors that make them vulnerable and attractive for cyber criminals (CBC News, 2021).
Keywords: ransomware; cyberattacks; healthcare; hospitals